Conceptualizing the complexity of reflective practice in education - Mohamed, Misrah; Rashid, Radzuwan Ab; Alqaryouti, Marwan Harb (Frontiers in Psychology, 2022)
In higher education, reflective practice has become a dynamic, participatory, and cyclical process that contributes to educators’ professional development and personal growth. While it is now a prominent part of educators, many still find it challenging to apply the concept for it carries diverse meaning for different people in different contexts. This article attempts to (re)conceptualize the complexity of reflective practice in an educational context. Scholars in this field have taken different approaches to reflective practice, but all these approaches consist of four main components in common: (i) reflecting; (ii) planning for future action; (iii) acting; and (iv) evaluating the outcomes. We extend the existing literature by proposing a model which integrates these four components with three key aspects of reflection: problem-solving, action orientation, and criticality. The novelty of this model lies within its alignment of the three key aspects with different levels of criticality in a comprehensive framework with detailed descriptors provided. The model and its descriptors are useful in guiding individuals who directly or indirectly involve in critical reflection, especially educators, in appraising their levels of criticality and consequently engage in a meaningful reflection.